PHYSIOLOGICAL EFFECTS AFTER EXPOSURE TO HEAT: A BRIEF LITERATURE REVIEW - Cornelis P. Bogerd; Hein A.M. Daanen (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Many employees are exposed to heat stress during their work. Although the direct effects of heat are well reported, the long term physiological changes after heat exposure are hardly described. The present manuscript addresses these issues in the form of a brief literature review. Repeated heat exposure results in heat acclimatization, these physiological adaptations decay gradually afterwards, re-increasing the vulnerability to heat injuries. Repeated heat exposure may lead to kidney damage (related to dehydration) and reduced efficiency of the reproductive system. A history of heat stroke may increase the sensitivity to heat illness. The increased susceptibility possibly indicates an impaired thermoregulatory system resulting from a heat stroke, or a genetic predisposition prior to the first heat stroke.